Self‐reported sleep quality and exercise in polycystic ovary syndrome: A secondary analysis of a pilot randomized controlled trial. (6th March 2023) - Benham, Jamie L.; Booth, Jane E.; Goldfield, Gary; Friedenreich, Christine M.; Rabi, Doreen M.; Sigal, Ronald J.
Abstract: Objective: To examine the proportion of participants with poor sleep quality, evaluate the associations between sleep quality and anthropometric and cardiometabolic health markers, and evaluate the effect of high intensity interval training (HIIT) and continuous aerobic exercise training (CAET) on sleep quality in polycystic ovary syndrome (PCOS). Design: Secondary analysis of a pilot randomized controlled trial. Patients: Women with PCOS aged 18–40 years. Measurements: The Pittsburgh Sleep Quality Index (PSQI) was measured at baseline and following a 6‐month exercise intervention. A PSQI score >5 indicates poor sleep. Linear regression was used to evaluate the associations between PSQI score and anthropometric and cardiometabolic health markers, and the effect of exercise training on these associations. Results: Thirty‐four participants completed the PSQI at baseline, and 29 postintervention: no‐exercise control ( n  = 9), HIIT ( n  = 12) and CAET ( n  = 8). At baseline, 79% had poor sleep quality. Baseline PSQI score was positively correlated with body mass index, waist circumference, body weight, haemoglobin A1c and insulin resistance. Mean PSQI score changes were −0.4 (SD 1.1), −0.7 (SD 0.6) and −0.5 (SD 0.9) for control, HIIT and CAET, respectively. For HIIT participants, change in PSQI score was associated with changes in body weight ( B  = .27, 95% CI 0.10–0.45) and waist circumference ( B  = .09, 95% CI 0.02–0.17). Conclusion: Most participants had poor sleep quality which was associated with poorer anthropometric and cardiometabolic health markers. There were no statistically significant changes in PSQI score with exercise training. With HIIT training, decreases in the sleep efficiency score were associated with reductions in body weight and waist circumference. Further studies are needed to determine the effect of exercise training on sleep quality.